Temporal instability of curved viscous fibers with a radial electric field - Alsharif, Abdullah M; Părău, Emilian I (IMA journal of applied mathematics, 2022)
Abstract One-dimensional equations are derived for a rotating viscous slender liquid jet in a radial electric field using asymptotic methods. The trajectory of the curved Newtonian liquid jets is found by solving the nonlinear one-dimensional equations. The temporal instability of the steady solutions is analysed. It was found that the electric force enhances the growth rate and increases its corresponding maximum wavenumber.